A rat subchronic study transcriptional point of departure estimates a carcinogenicity study apical point of departure. (January 2021) - Bianchi, Enrica; Costa, Eduardo; Yan, Zhongyu (June); Murphy, Lynea; Howell, Jessica; Anderson, Donna; Mukerji, Push; Venkatraman, Anand; Terry, Claire; Johnson, Kamin J.
Abstract: Considerations of human relevance and animal use are driving research to identify new approaches to inform risk assessment of chemicals and replace guideline-based rodent carcinogenicity tests. Here, the hypothesis was tested across four agrochemicals that 1) a rat 90-day transcriptome-based BEPOD is protective of a rat carcinogenicity study and 2) a subchronic liver or kidney BEPOD would approximate a cancer bioassay apical POD derived from other organs and a rat subchronic BEPOD would approximate a mouse cancer bioassay apical POD. Using RNA sequencing and BMDExpress software, liver and/or kidney BEPOD values were generated in male rats exposed for 90 days to either Triclopyr Acid, Pronamide, Sulfoxaflor, or Fenpicoxamid. BEPOD values were compared to benchmark dose-derived apical POD values generated from rat 90-day and rodent carcinogenicity studies. Across all four agrochemicals, findings showed that a rat 90-day study BEPOD approximated the most sensitive apical POD (within 10-fold) generated from the 90-day rat study and long-term rodent carcinogenicity studies. This study supports the conclusion that a subchronic transcriptome-based BEPOD could be utilized to estimate an apical POD within a risk-based approach of chronic toxicity and carcinogenicity agrochemical assessment, abrogating the need for time- and resource-intensive rodent carcinogenicity studies and minimizing animal testing. Highlights: For agrochemicals, a subchronic study transcriptome POD estimates a carcinogenicity study apical POD. Optimal concordance between a transcriptome POD and a apical POD is obtained within the same species and sex. Optimal estimation of a carcinogenicity study apical POD is obtained by deriving a transcriptome POD from the target organ.